One-pot, uracil-DNA-glycosylase-aided, and multi-indicator nanobiosensor detection platform for identifying Brucella melitensis from the Brucella spp - Xinggui Yang; Yue Wang; Sha Mao; Ying Liu; Fengming Chen; Junfei Huang; Xiaoyan Zeng; Hai Jiang; Shijun Li (BMC Microbiology)
Abstract Background Brucellosis, a zoonotic chronic contagious disease caused by Brucella spp., is primarily associated with species such as Brucella melitensis (B. melitensis) and B. abortus, among which B. melitensis is recognized as the most virulent in causing human brucellosis. Methods Herein, we report a newly “one-pot” detection protocol for the identification of B. melitensis from the genus Brucella using the multiplex multiple cross-displacement amplification (MCDA) combined with dUTP-assisted uracil-DNA-glycosylase (UDGase) and gold nanoparticles lateral flow assay (AuNPs-LFA) biosensor (termed mMCUDA). Two sets of MCDA primers targeting the bcsp31 and BMEII0466 genes were designed. Various clinical isolates and whole blood samples were used to optimize and evaluate the mMCUDA assay. Results The optimal condition for mMCUDA is 65℃ for 60 min. The limit of detection (LoD) of the mMCUDA assay was confirmed to be 7.5 fg/reaction. The mMCUDA assay can accurately identify B. melitensis from the Brucella spp. used in the study, and no cross-reaction with non-target pathogens was observed. The protocol has a powerful capability to eliminate carryover contamination (approximately 1.5 × 10−13 g/reaction). Conclusions Taken-together, these investigative data demonstrated that the mMCUDA assay is a straightforward, one-pot, easy-to-obtain, friendly-to-use, and highly specific detection platform, which can be used as a useful potential screening tool in clinical applications.